Poly(thymine)-templated fluorescent copper nanoparticles for label-free detection of N-acetylcysteine in pharmaceutical samples1. Issue 15 (7th August 2015) - Wang, Hai-Bo; Zhang, Hong-Ding; Chen, Ying; Ou, Li-Juan; Liu, Yan-Ming
<x xml:space="preserve">Abstract</x> A simple, label-free, sensitive fluorescence sensing strategy is reported for N-acetylcysteine detection by using poly T-templated Cu NPs as fluorescent probes.